Preliminary GC-MS profiling of bioactive compounds in Muntingia Calabura from the rural area of Bukit Besi - Ab Rahman, Nur Syukriah; Ahmad, Muhammad Hazim; Othman, Qistina Liyana; Mohamad Nizam, Nur Hanisah; Mohd Daud, Nurizzati (Universiti Teknologi MARA Shah Alam, 2025)
Muntingia calabura is a medicinal plant commonly found along roadsides in Malaysia and is traditionally believed to possess various therapeutic activities. Although it has been widely utilised in traditional medicine and several pharmacological properties have been reported, most studies have relied on crude extracts without detailed characterisation of the bioactive constituents. Therefore, the present study aimed to identify the bioactive compounds in the fruit, leaves, and stem bark using Gas Chromatography-Mass Spectroscopy (GC-MS). Each part of the plant was extracted using the Soxhlet technique and hexane and petroleum ether as a solvent. GC-MS analysis revealed seven (7) compounds using petroleum ether and ten (10) compounds in hexane extract in fruit parts; ten (10) compounds in petroleum ether and seventeen (17) compounds using hexane in leaf parts; and ten (10) compounds in petroleum ether and fifteen (15) compounds using hexane in stem bark parts. The prime compound found in fruit is 2-Methyl-Z, Z-3,13-octadecadienol (64.27%) using petroleum ether, while it is L- (+)-Ascorbic acid 2,6-dihexadecanoate (29.95%) when using hexane. For leaves, both solvents showed a similar most extracted compound, which is 9-Octadecenoic acid, 1,2,3-propanetriyl ester (42.29% with petroleum ether and 25.34% with hexane). In stem bark, the most extracted compound is 2-Methyl-Z, Z-3,13-octadecadienol (29.88%) (fatty alcohol) for petroleum ether, while for hexane extract, it is 2H-1- Benzopyran-6-ol,3,4-Dihydro-2,5,7,8-Tetramethyl-2-(4,8,12-Trimethyl Tridecyl) (31.88%). These findings indicate the diverse bioactive compound was found in different parts of Muntingia calabura, emphasising the need for further pharmacological and biological studies to validate its therapeutic claim.